Effect of astaxanthin in type-2 diabetes -induced APPxhQC transgenic and NTG mice - Joshua Adekunle Babalola; Anika Stracke; Tina Loeffler; Irene Schilcher; Spyridon Sideromenos; Stefanie Flunkert; Joerg Neddens; Ake Lignell; Manuela Prokesch; Ute Pazenboeck; Herbert Strobl; Jelena Tadic; et al. (Elsevier, 2024)
Objectives: Aggregation and misfolding of amyloid beta (Aβ) and tau proteins, suggested to arise from post-translational modification processes, are thought to be the main cause of Alzheimer's disease (AD). Additionally, a plethora of evidence exists that links metabolic dysfunctions such as obesity, type 2 diabetes (T2D), and dyslipidemia to the pathogenesis of AD. We thus investigated the combinatory effect of T2D and human glutaminyl cyclase activity (pyroglutamylation), on the pathology of AD and whether astaxanthin (ASX) treatment ameliorates accompanying pathophysiological manifestations. Methods: Male transgenic AD mice, APPxhQC, expressing human APP751 with the Swedish and the London mutation and human glutaminyl cyclase (hQC) enzyme and their non-transgenic (NTG) littermates were used. Both APPxhQC and NTG mice were allocated to 3 groups, control, T2D-control, and T2D-ASX. Mice were fed control or high fat diet ± ASX for 13 weeks starting at an age of 11-12 months. High fat diet fed mice were further treated with streptozocin for T2D induction. Effects of genotype, T2D induction, and ASX treatment were evaluated by analysing glycemic readouts, lipid concentration, Aβ deposition, hippocampus-dependent cognitive function and nutrient sensing using immunosorbent assay, ELISA-based assays, western blotting, immunofluorescence staining, and behavioral testing via Morris water maze (MWM), respectively. Results: APPxhQC mice presented a higher glucose sensitivity compared to NTG mice. T2D-induced brain dysfunction was more severe in NTG compared to the APPxhQC mice. T2D induction impaired memory functions while increasing hepatic LC3B, ABCA1, and p65 levels in NTG mice. T2D induction resulted in a progressive shift of Aβ from the soluble to insoluble form in APPxhQC mice. ASX treatment reversed T2D-induced memory dysfunction in NTG mice and in parallel increased hepatic pAKT while decreasing p65 and increasing cerebral p-S6rp and p65 levels. ASX treatment reduced soluble Aβ38 and Aβ40 and insoluble Aβ40 levels in T2D-induced APPxhQC mice. Conclusions: We demonstrate that T2D induction in APPxhQC mice poses additional risk for AD pathology as seen by increased Aβ deposition. Although ASX treatment reduced Aβ expression in T2D-induced APPxhQC mice and rescued T2D-induced memory impairment in NTG mice, ASX treatment alone may not be effective in cases of T2D comorbidity and AD.